The "highway effect" on school enrollment the case of SCTEX and TPLEX - Realeza, Collete P.; Santos, Elijah C.; Monsod, Toby Melissa C.
In this study, we examine the effect of highway investments, specifically that of the Subic-Clark-Tarlac Expressway and the Tarlac-Pangasinan-La Union Expressway, on the enrollment rates of the municipalities within the provinces of Bataan, Pampanga, Tarlac, Nueva Ecija, and Pangasinan. On the one hand, highways expose people to greater employment opportunities in other regions and may lead to an increase in the opportunity costs of education. On the other hand, highways can lower transport costs, directly lowering the costs of studying, which may lead to increased attendance. After employing a modified two-way fixed effects model with multiple time periods and treatment groups, we find that these specific highway investments did not affect the enrollment rates of younger students. Unexpectedly, we also find that the enrollment rates of older students were not affected. This may be explained by the trend of enrollment rates of older students post-K-12 implementation.